2014
DOI: 10.1127/0003-5548/2014/0406
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between birth weight, adiposity rebound and overweight at the age of 17 years (results of the Lithuanian longitudinal growth study, 1990–2008)

Abstract: The purpose of this study was to investigate the relationship between overweight and obesity at the age of 17 years with a birth weight and time of an adiposity rebound. The results were based on data (N = 1535) collected from the personal health records of children born in 1990 in Vilnius city and region. The further growth of newborns with normal (3000 - 3999 g), suboptimal (2500 - 2999 g) and large (≥ 4000 g) birth weight was analyzed. Statistically significant results (p < 0.05) were obtained in girls: at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A number of studies support that a greater intake of UPF is associated with overweight or obesity [17][18][19][20][21][22][23]. However, in our study, UPF consumption was not significantly associated with BMI values or the risk of overweight and obesity among children after the adjustment for confounding factors, which is in accordance with a prior cross-sectional study based on the UK National Diet and Nutrition Survey [48] and follow-up studies in Brazil and Portugal [49,50].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A number of studies support that a greater intake of UPF is associated with overweight or obesity [17][18][19][20][21][22][23]. However, in our study, UPF consumption was not significantly associated with BMI values or the risk of overweight and obesity among children after the adjustment for confounding factors, which is in accordance with a prior cross-sectional study based on the UK National Diet and Nutrition Survey [48] and follow-up studies in Brazil and Portugal [49,50].…”
Section: Discussionsupporting
confidence: 89%
“…The emerging evidence supports that birth weight is associated with later BMI [17,18], BMI z-score [19,20] and risk of overweight or obesity among children [21][22][23]. The epidemiological studies have consistently identified that high birth weight (HBW) is related to increased BMI [17] and the risk of overweight or obesity in childhood [24][25][26][27].…”
Section: Introductionmentioning
confidence: 94%
“…Most term SGA babies showed significantly rapid weight gain or catch-up growth (CUG) compensating for intrauterine restraint within the first two years of life [ 2 ]. Nevertheless, overweight and premature appearance of adiposity rebound (AR), which was reported to be a predictive marker of obesity and other metabolic syndromes in adulthood [ 3 5 ], can be observed in early childhood of SGA as well [ 6 ]. Growing evidences have suggested an increased long-term risk of excessive adiposity and the accompanying comorbidities across the life among infants who have been found to be with intrauterine growth restriction followed by rapid weight gain in infancy [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are lots of evidence about the risk factors for becoming overweight during childhood: gender (Steur et al, 2011), big birth weight (Pereira-Freire, Lemos, de Sousa, Meneses, & Rondo, 2015;Sacco, de Castro, Euclydes, Souza, & Rondo, 2013;Suchomlinov & Tutkuviene, 2014;Woo Baidal et al, 2016), relationship with parents (Blewitt, Bergmeier, Macdonald, Olsson, & Skouteris, 2016), parental excess weight and education level (Parikka et al, 2015;Smetanina et al, 2015), passive smoking (Steur et al, 2011), the number and gender of siblings (Mosli et al, 2016), breakfast skipping and lower meals frequency (Smetanina et al, 2015). Depression can be the reason as well as the consequences of the excess weight (Russell-Mayhew, McVey, Bardick, & Ireland, 2012).…”
mentioning
confidence: 99%